The African American urban male's journey to success : psychoanalytic perspectives on race, gender and social class - Goedert, Mead (Lexington Books, 2016)
"The African American Urban Male's Journey to Success is part of a growing effort within psychoanalytic thought to address psychoanalysis' historical negligence of marginalized subjects and sociocultural dynamics within theory and practice. This book utilizes a psychoanalytic framework to portray and examine the subjective experiences of five professional African American men who transcended their origins in urban poverty, thus shedding light on a grossly overlooked demographic."--Provided by publisher